2006
DOI: 10.1007/s10661-006-1069-6
|View full text |Cite
|
Sign up to set email alerts
|

Trace Level Determination of U, Zn, Cd, Pb and Cu in Drinking Water Samples

Abstract: The concentration of uranium has been assessed in drinking water samples collected from different locations in Bathinda district, Punjab, India. The water samples are taken from hand pumps and tube wells. Uranium is determined using fission track technique. Uranium concentration in the water samples varies from 2.23+/- 0.05 to 87.05+/- 0.29 microg/L. These values are compared with safe limit values recommended for drinking water. The uranium concentration in almost all drinking water samples is found to be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…It has also been observed that Zn with average value of 833.8 mgl À1 has been found well above the permissible limit 10 mgl À1 given by the WHO. This corroborate the pervious study carried out by Kumar, Singh, and Mahajan (2006), where it has been reported to be observed in the range 3e1044 mgl À1 .…”
Section: Resultssupporting
confidence: 93%
“…It has also been observed that Zn with average value of 833.8 mgl À1 has been found well above the permissible limit 10 mgl À1 given by the WHO. This corroborate the pervious study carried out by Kumar, Singh, and Mahajan (2006), where it has been reported to be observed in the range 3e1044 mgl À1 .…”
Section: Resultssupporting
confidence: 93%
“…However when compared with USEPA (2003) recommended level of 30 μg l −1 , all the analyzed samples from Upper Siwalik region and adjoining area of Punjab revealed uranium values below the safe limit. The uranium concentrations higher than 20 μg l −1 were generally observed in water samples coming from uranium rich zones (Kumar et al 2006). All the water samples have values less than 20 μg l −1 so these are safe for drinking purposes.…”
Section: Resultsmentioning
confidence: 98%
“…The values of R (2) were 0.9716, 0.9699 and 0.9982 for lead (II), cadmium (II) and copper (II) ions, respectively, indicating the validity of the model. Table 4 shows similar results reported previously for biosorption of cadmium and other heavy metals.…”
Section: Discussionmentioning
confidence: 76%
“…Toxic heavy metals are released in the environment from a number of industries such as mining, plating, dyeing, automobile manufacturing, and metal processing (1). Cadmium is a toxic metal that occurs naturally in the environment and is considered as a pollutant emanating from industrial and agricultural sources (2). Adsorption is one of the methods for the removal of heavy metals from wastewater.…”
Section: Introductionmentioning
confidence: 99%